2008
DOI: 10.1373/clinchem.2007.097360
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation in Atherosclerosis: From Vascular Biology to Biomarker Discovery and Risk Prediction

Abstract: Recent investigations of atherosclerosis have focused on inflammation, providing new insight into mechanisms of disease. Inflammatory cytokines involved in vascular inflammation stimulate the generation of endothelial adhesion molecules, proteases, and other mediators, which may enter the circulation in soluble form. These primary cytokines also induce production of the messenger cytokine interleukin-6, which stimulates the liver to increase production of acute-phase reactants such as C-reactive protein. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
597
0
37

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 798 publications
(648 citation statements)
references
References 169 publications
(134 reference statements)
14
597
0
37
Order By: Relevance
“…We selected several proinflammatory molecules considered to be representative inflammatory mediators involved in atherogenesis to test this hypothesis 8, 9, 10. Of these selected mediators, we observed that IL‐1 β expression was significantly higher in clots from patients with large artery atherosclerosis than in those with either cardioembolism or undetermined etiology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We selected several proinflammatory molecules considered to be representative inflammatory mediators involved in atherogenesis to test this hypothesis 8, 9, 10. Of these selected mediators, we observed that IL‐1 β expression was significantly higher in clots from patients with large artery atherosclerosis than in those with either cardioembolism or undetermined etiology.…”
Section: Discussionmentioning
confidence: 99%
“…Large artery atherosclerosis is an important etiology of acute ischemic stroke and inflammation is well‐known to play a pivotal role in all stages of atherosclerosis, from lesion initiation to progression and destabilization 8. The pathogenesis of atherosclerosis is crucially influenced by inflammatory mediators such as proinflammatory cytokines and extracellular proteases secreted by smooth muscle cells, endothelial cells, and immune cells 8, 9, 10.…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing evidence that inflammation plays an important role in atherosclerosis and its clinical complications: cardiovascular disease (CVD) including coronary heart disease (CHD) and ischaemic stroke [1]. Previous reports from the prospective Caerphilly Study have shown that circulating inflammatory markers including fibrinogen, plasma viscosity and leucocyte count [2,3]; C-reactive protein (CRP) [4]; and ␣1-antitrypsin and ␣2-macroglobulin [5] are associated with CHD risk.…”
Section: Introductionmentioning
confidence: 99%
“…A large body of evidence also indicates a central role for inflammation in atherosclerotic disease [14,15]. Multiple epidemiological studies have associated C-reactive protein (CRP), an acute-phase reactant and marker of inflammation, with CVD risk [16].…”
Section: Introductionmentioning
confidence: 99%